Pengaruh Model Inquiry Learning Berbantuan Media Wordwall Terhadap Hasil Belajar IPAS Pada Materi Bentuk - Bentuk Energi Kelas III SD - Pertiwi, Anggun Rifka; Rukmana, Diki (Institut Agama Islam Daruttaqwa Gresik, 2025)
This study was motivated by the low learning outcomes of third-grade elementary students in Natural and Social Sciences (IPAS), particularly in the topic of forms of energy. Students experienced difficulties in concentrating during lessons, especially during the day, and the lack of hands-on experiments made it hard for them to fully understand the concepts. The average student score was only 68, below the Minimum Mastery Criteria (KKTP) of 75. Therefore, this study aimed to determine the effect of the Inquiry Learning model assisted by Wordwall media on students’ learning outcomes in the topic of energy forms. The research employed a quantitative method with a pre-experimental design (one group pre-test and post-test), using purposive sampling to select third-grade class III B as the sample. Instrument validity was tested using Pearson correlation, and reliability was measured with Cronbach’s Alpha. Data were analyzed using normality and hypothesis tests. The results showed a significant effect (p = 0.001 < 0.05) of the Inquiry Learning model with Wordwall in improving students’ understanding. The model encouraged active participation, aligned with students' learning styles, and created a more engaging learning environment.